Comparison of Surgical Outcomes After Open- and Double-Door Laminoplasties for Patients with Cervical Ossification of the Posterior Longitudinal Ligament: A Prospective Multicenter Study - Nagoshi, Narihito; Yoshii, Toshitaka; Egawa, Satoru; Sakai, Kenichiro; Kusano, Kazuo; Nakagawa, Yukihiro; Hirai, Takashi; Wada, Kanichiro; Katsumi, Keiichi; Fujii, Kengo; Kimura, Atsushi; Furuya, Takeo; et al. (Spine (Philadelphia, Pa. 1976), 2021)
A prospective multicenter study. To evaluate and compare the surgical outcomes after open-door (OD) and double-door (DD) laminoplasties in subjects with cervical ossification of the posterior longitudinal ligament (OPLL). Although previous studies compared clinical results after OD and DD laminoplasties, they were performed at a single institution with a relatively small sample size targeting mixed pathologies, including cervical spondylotic myelopathy. This study was performed by the Japanese Multicenter Research Organization for Ossification of the Spinal Ligament. A total of 478 patients with myelopathy caused by cervical OPLL from 28 institutions were prospectively registered from 2014 to 2017 and followed up for 2 years. Of these, 41 and 164 patients received OD and DD laminoplasties, respectively. Demographic information, medical history, and imaging findings were collected. Clinical outcomes were assessed using the cervical Japanese Orthopaedic Association (JOA), JOA Cervical Myelopathy Evaluation Questionnaire (JOACMEQ), and visual analog scale (VAS) scores. Age, sex, symptom duration, and comorbidities were not significantly different between the groups. Segmental ossification was the most frequent in both groups. No significant differences in K-line type, canal occupying ratio, C2-C7 angles, and range of motion (ROM) were found. Both procedures reduced the cervical ROM postoperatively. A comparable frequency of perioperative complications was observed between the groups. The cervical JOA scores showed a similar improvement at 2 years postoperatively. The reduction in VAS score for neck pain was favorable in the OD group (P = 0.02), while other pain assessments did not show any significant differences between the groups. The functional outcomes assessed using the JOACMEQ presented equivalent effective rates. The results demonstrated almost comparable surgical outcomes between OD and DD laminoplasties. Laminoplasty is a valuable technique as a therapeutic option for cervical OPLL.Level of Evidence: 5.